Acute care models for hip fracture treatment vs post-acute rehabilitation services in older adults after hip fracture: A comparative claims data analysis from Germany - Clemens Becker; Kilian Rapp; Dietrich Rothenbacher; Claudia Schulz; Hans-Helmut König; Gisela Büchele (Medical Journals Sweden, 2020)
Objective: Acute geriatric care (geriatric early rehabilitative treatment) and sub-acute (inpatient) geriat-ric rehabilitation are delivered to geriatric patients in Germany after hip fracture. The aim of this study was to compare patients' outcomes after hip fracture between 3 German federal states (Hesse, Bavaria, and Baden-Wuerttemberg) that nearly exclusively offered one of the two geriatric care systems. Design: Retrospective cohort study with patient-related health insurance claims data. Patients: Analyses were performed with data from 2009-2012 of over 30,000 patients aged ≥80 years with incident hip fracture. Methods: Primary outcomes: "increase in care dependency", "nursing home admission"; secondary outcomes: "rehospitalization", "mortality". Multivariate regression models were applied. Results: Compared with Hesse, the state with acute geriatric care, the risks of an "increase in care dependency" were lower in Bavaria (adjusted ratio = 0.84; 95% confidence interval (95% CI) 0.81-0.87) and Baden-Wurttemberg (0.88; 0.85-0.92), the 2 federal states with sub-acute geriatric rehabilitation. A reduction in the risk of nursing home admission was observed in Baden-Wuerttemberg (0.77; 95% CI 0.69-0.87), but not in Bavaria. Rehospitalization rates were lower in Bavaria and Baden-Wuerttemberg compared with Hesse. There was no difference in mortality. Conclusion: Some, but not all, outcomes were more favourable in the federal states with sub-acute geriatric rehabilitation than in the federal state with acute geriatric care.